2018
DOI: 10.3390/w10091270
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Operation Program of a Hydropower Plant Based on Minimizing the Principal Stress: Haditha Dam Case Study

Abstract: Dam operation and management have become more complex recently because of the need for considering hydraulic structure sustainability and environmental protect on. An Earthfill dam that includes a powerhouse system is considered as a significant multipurpose hydraulic structure. Understanding the effects of running hydropower plant turbines on the dam body is one of the major safety concerns for earthfill dams. In this research, dynamic analysis of earthfill dam, integrated with a hydropower plant system conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…The current authors' observation on the water loss indicates that the reservoir recharges the groundwater and this is a good indication for intensively karstified area of the reservoir. Li et al (2018) performed a dynamic analysis of the Haditha earthfill dam, integrated with a hydropower plant system containing six vertical Kaplan turbines. They concluded that understanding the effects of running hydropower plant turbines on the dam body is one of the major safety concerns for the earthfill dam, besides other safety concerns such as karstification.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The current authors' observation on the water loss indicates that the reservoir recharges the groundwater and this is a good indication for intensively karstified area of the reservoir. Li et al (2018) performed a dynamic analysis of the Haditha earthfill dam, integrated with a hydropower plant system containing six vertical Kaplan turbines. They concluded that understanding the effects of running hydropower plant turbines on the dam body is one of the major safety concerns for the earthfill dam, besides other safety concerns such as karstification.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Haditha Dam is an earthfall Dam located at 34 • 120 latitudes and 42 • 210 longitudes on the narrow stretch of the Euphrates River, about 8 km northwest of Haditha city, which Located about 270 km northwest of Baghdad .Haditha Dam was constructed for multi-functional purposes and is used for hydroelectricity generation, regulating the flow of the Euphrates River and irrigation of field water (see Figure 1). After the Mosul Dam, the Haditha Dam is considered the second largest electrical supplier of power [27].…”
Section: Haditha Dam Case Studymentioning
confidence: 99%
“…Euphrates River [27] The total length of the Haditha dam is around 9 km, and the maximum height is 57 m high from the deepest point of the river. The total Dam storage is 6 trillion cubic meters at a normal operating level.…”
Section: Figure 1 Map Of Location and Layout Of Haditha Dam On Thementioning
confidence: 99%
“…In the case of run-off-the-river dams, the potential energy in the flowing water is converted by a powerhouse into electrical energy [68]. The two factors that determine the annual potential power output of any hydropower plant are the available head and water discharge [69,70]. In the powerhouse, the potential energy of the flowing water is converted via a simple concept to a force that turns the turbine; the turning of the turbine provides the required mechanical energy to power a generator for electricity generation [12].…”
Section: Powerhousementioning
confidence: 99%